2016
DOI: 10.15407/fz62.05.076
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Gadolinium Orthovanadate Nanoparticles by Neonatal Induced Reproductive Disease in Male Rats

Abstract: Вивчали ефективність наночастинок ортованадату гадолінію (НЧ GdVO4

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Many studies have demonstrated that downscaled systems of GdVO 4 exhibit multiple characteristics in the field of biomedical applications: photodynamic therapy, radiation therapy, drug delivery etc. (Teo et al, 2016;Belkina et al, 2016;Dong et al, 2015). There are many preparation methods that have been reported in the literature for obtaining GdVO 4 such us sol-gel (Chumha et al, 2014), edge-defined film-fed (EFG) (Epelbaum et al, 1998), Czochralski (Loiko et al, 2013), co-precipitation (Vosoughifar, 2017), hydrothermal (Szczeszak et al, 2014;Mahapatra & Ramanan, 2005), solvothermal (Liang et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have demonstrated that downscaled systems of GdVO 4 exhibit multiple characteristics in the field of biomedical applications: photodynamic therapy, radiation therapy, drug delivery etc. (Teo et al, 2016;Belkina et al, 2016;Dong et al, 2015). There are many preparation methods that have been reported in the literature for obtaining GdVO 4 such us sol-gel (Chumha et al, 2014), edge-defined film-fed (EFG) (Epelbaum et al, 1998), Czochralski (Loiko et al, 2013), co-precipitation (Vosoughifar, 2017), hydrothermal (Szczeszak et al, 2014;Mahapatra & Ramanan, 2005), solvothermal (Liang et al, 2011).…”
Section: Introductionmentioning
confidence: 99%